Detection of Entamoeba Gingivalis in Diseased and Healthy Periodontal Sites among Cancer Patients in Thi-Qar Province - Adnan, Raed; Al-Aboody, Bassad A. (University of Thi-Qar Journal of Science, 2024)
Periodontitis, being one of the most common illnesses in the world represents a significant public health concern. The aims of this study are to determine Entamoeba gingivalis prevalence in cancer patients compared to healthy individuals (as a control), study some of the factors (such as diabetes and smoking) affecting the presence of this parasite, in cancer patients and control in the Thi-Qar Province of Iraq. For detection of Entamoeba gingivalis samples, were collected from cancer patients (different types of cancer) and control, including individuals with and without periodontitis, from Al- Haboubi Teaching Hospital during the period from August 2023 to December 2023. The current study showed the overall infection rate of E. gingivalis was 46.33% in all study samples. The results also showed that the presence of Trophozoite and the cyst-like trophozoite of E. gingivalis was found in 7.19% of positive samples (n = 10/139). This study indicated that there are significant differences (p<0.05) in the percentage of E. gingivalis infections in individuals with periodontitis, diabetes, or smoking ; these have a higher infection rate than those who without, in both the cancer patients and control. No significant differences p<0.05 were seen in the infection rate of E. gingivalis between males and females in both groups. The results showed that the infection rate of E. gingivalis was highest in the age group ≥61 and lowest in the age group ≤30 for both cancer patients and the control group, regardless of whether they had periodontitis or not.